Giant lupus vulgaris: A rare presentation - S Sacchidanand; S Sharavana; M Mallikarjun; H V Nataraja (Wolters Kluwer Medknow Publications, 2012)
Cutaneous tuberculosis continues to be an important public health problem even with the availability of highly effective anti-tuberculous drugs. It constitutes 0.1% of all cases of extrapulmonary tuberculosis. Lupus vulgaris is the most common form of cutaneous tuberculosis that occurs in previously sensitized individuals with a moderate degree of immunity against tubercle bacilli. The different types of lupus vulgaris include plaque, ulcerative, vegetative, papular and nodular, and tumor forms. A 40-year-old man presented with large multiple plaques over right upper limb, right side of chest and back, and right lower limb for the past 30 years. Histopathology showed numerous noncaseating granulomas with Langhan's type of giant cells. The Mantoux test showed strong positivity and there was excellent response to anti-tuberculous treatment. This case is being reported because of its extreme chronicity of 30 years duration, unusually large size and multiplicity of lesions.